The identity `(cos x + cos y)^2 + (sin x – sin y)^2 = 2 + 2cos(x + y)` has to be proved.

Start from the left hand side.

`(cos x + cos y)^2 + (sin x – sin y)^2`

=> `cos^2 x` + `cos^2 y` + `2*cos x*cos...

## Unlock

This Answer NowStart your **48-hour free trial** to unlock this answer and thousands more. Enjoy eNotes ad-free and cancel anytime.

Already a member? Log in here.

The identity `(cos x + cos y)^2 + (sin x – sin y)^2 = 2 + 2cos(x + y)` has to be proved.

Start from the left hand side.

`(cos x + cos y)^2 + (sin x – sin y)^2`

=> `cos^2 x` + `cos^2 y` + `2*cos x*cos y` + `sin^2 x` + `sin^2 y` - `2*sin x*sin y`

=> `cos^2 x + sin^2 x` + `cos^2 y + sin^2 y` + `2*cos x*cos y - 2*sin x*sin y`

=> `1 + 1 + 2*(cos x*cos y - sin x*sin y)`

Use the relation `cos(x + y) = cos(x)cos(y) - sin(x)sin(y)`

=> 2 + 2*cos (x + y)

**This proves that (cos x + cos y)^2 + (sin x – sin y)^2 = 2 + 2cos(x + y)**